Peran Pancasila dalam Membentuk Pola Pikir Anak SD di Tengah Perkembangan Peradaban - Wiwin Hidayanti Gea; Friska Delviana Silaban; Yosnida Sianturi; Yuni Anggriani Br Nainggolan; Willy Partogi Nainggolan (Concept: Journal of Social Humanities and Education, 2025)
Pancasila as the foundation of the state has an important role in shaping the mindset and character of children from an early age, especially at the elementary school level. In the challenging era of globalization, Pancasila-based education is the main foundation in instilling national and moral values. This study aims to explore the role of Pancasila in shaping the mindset of elementary school children and strategies that can be applied in learning so that its values can be internalized effectively. The method used in this study is a literature study by reviewing various relevant scientific articles. The results of the study indicate that an experience-based learning approach, the active role of teachers as role models, and synergy between schools, families, and communities are key factors in instilling Pancasila values. In addition, the challenges of globalization and technological developments require strengthening Pancasila-based digital literacy so that children are able to filter information wisely. Thus, Pancasila-based character education is a strategic element in forming a young generation that has integrity, social responsibility, and critical thinking skills in facing changing times.